Penggunaan Metode Rapid Application Development (RAD) untuk Merancang Aplikasi Absensi QR Code Berbasis Website - Endri Mujiono; Yani Parti Astuti; Etika Kartikadarma; Edy Mulyanto; Erlin Dolphina; Sindhu Rakasiwi (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This study aims to design and develop a QR Code-based attendance application using the Rapid Application Development (RAD) method, which is implemented at Bina Utama Kendal Vocational High School. The application was created to overcome the limitations of the manual attendance system currently in use, such as vulnerability to data loss, difficulties in maintaining accurate records, and inefficiency in attendance recapitulation. The RAD method was chosen because it emphasizes user involvement throughout the development process, ensuring that the resulting system meets user needs. The development stages included requirement planning, design, system development, and implementation. This web-based attendance application uses QR Code technology to record student attendance quickly, accurately, and in real time. Each student’s QR Code is scanned to mark their presence, which minimizes errors and prevents attendance fraud. In addition, the system includes features for managing student data, generating automatic attendance reports, and providing real-time monitoring for teachers and administrators.The system was tested using the Black Box method, which confirmed that all features function correctly and meet the requirements specified in the design phase. Furthermore, a user satisfaction survey conducted with 150 respondents (teachers, students, and staff) indicated a very high level of acceptance, with an average of 94.25% respondents strongly agreeing on the ease of use, accuracy, and benefits of this application. Overall, the study demonstrates that the QR Code-based attendance application significantly improves the efficiency, reliability, and accuracy of attendance management at Bina Utama Kendal Vocational High School.